Intersemiotic translation of the Immortal Life of Henrietta Lacks - Sanchez, Ana (Advances in Social Sciences Research Journal, 2018)
The main purpose of this paper is to present an innovative critical pedagogy to include a unit on social justice in the curriculum. This critical approach is an intersemiotic translation of the New York bestseller book ‘The Immortal Life of Henrietta Lacks” by Rebecca Skoot. Intersemiotic translation is to translate from a linguistic mode to another semiotic mode or vice versa. In this paper, students translated from a linguistic code, which was their first language, to other semiotic codes, which include pictures, symbols, photos and even a linguistic code, which was their second language-Spanish. The book ‘The immortal Life of Henrietta Lacks”, explores a wide variety of social topics such as discrimination based on gender, race and color among many others. The main purpose of having students do the multimodal translation and present it to class was to open a space for sharing students’ perspectives, to disrupt, de-mystify, critique, and question the status quo and to create awareness of the worldviews of those being silenced, marginalized and oppressed.